2018
DOI: 10.1038/s41435-018-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

IFN-λs inhibit Hantaan virus infection through the JAK-STAT pathway and expression of Mx2 protein

Abstract: Hantaan virus (HTNV), member of the newly defined Hantaviridae family, within the order Bunyavirales, can cause a hemorrhagic fever with renal syndrome with high fatality rates in humans. However, no specific antiviral agents are currently available for HTNV infection approved by the US Food and Drug Administration. Although interferon lambdas (IFN-λs) have been shown to induce an antiviral state against HTNV, the molecular mechanisms remain to be determined. In this study, we found that IFN-λs exerted its ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Human 293T cells and human HeLa cells were grown in DMEM supplemented with 10% fetal bovine serum (FBS) (Gibco) and 1% (w/v) penicillin/streptomycin. To achieve HeLa cells stably expressing MxB, HeLa cells were stably transduced with lentiviruses containing MxB and then selected by puromycin as we previously described [7]. Recombinant viruses were produced in 293T cells by cotransfecting psPAX2, pMD2.G and the pLV-CMV-EF1-GP based plasmids (at a ratio of 1:1:2).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Human 293T cells and human HeLa cells were grown in DMEM supplemented with 10% fetal bovine serum (FBS) (Gibco) and 1% (w/v) penicillin/streptomycin. To achieve HeLa cells stably expressing MxB, HeLa cells were stably transduced with lentiviruses containing MxB and then selected by puromycin as we previously described [7]. Recombinant viruses were produced in 293T cells by cotransfecting psPAX2, pMD2.G and the pLV-CMV-EF1-GP based plasmids (at a ratio of 1:1:2).…”
Section: Cell Linesmentioning
confidence: 99%
“…Human Myxovirus resistance protein 2 (Mx2/MxB), a member of the dynamin-like large GTPases that belong to the dynamin superfamily, was originally found to regulate cell-cycle progression and cytoplasmic-nuclear transport [1], but recently was demonstrated to inhibit the infection of various viruses, including HIV-1 [2][3][4], Herpesviruses [5,6], HTNV [7], HCV [8], HBV [9] and other lentiviruses such as SIV, EIAV and FIV [2]. Human MxB was reported to target the HIV-1 capsid protein (CA) after cell entry [10][11][12][13], to prevent uncoating [14], nuclear import of the viral pre-integration complex (PIC, composed of viral components include viral DNA, integrase (IN), nucleocapsid (NC), matrix (MA), viral protein R (Vpr), and reverse transcriptase (RT); several host proteins including lens epithelium-derived growth factor (LEDGF/p75), barrier-to-autointegration factor (BAF), and integrase interactor 1 (INI1) [15,16]) and subsequent chromosomal integration of the proviral DNA into the host genome, but did not affect reverse transcription [2-4, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, human population genetic analyses identified that the ancestral allele of Mx2 protects from HIV-1 infection and is associated with lower in vitro HIV-1 replication and increased Mx2 expression in response to IFN-α [191]. In addition to HIV, Mx2 is also able to restrict infections by other human viruses such as HSV-1 and 2 and Kaposi’s sarcoma-associated herpesvirus (KSHV) in the context of IFN-I [192] and Hantaan virus in response to IFN-λ [193].…”
Section: Restriction Factors Belonging To the Interferon Stimulatementioning
confidence: 99%
“…Following IFNs binding to IFNRs, STATs are phosphorylated by activated JAKs or other tyrosine kinases and translocate to the cell nuclei to induce gene transcription. The importance of the JAK/STAT IFN signaling in restricting replication of different viruses has been observed with enteric viruses such as hepatitis E virus, rotavirus and human norovirus ( 70 , 71 ), whereas inhibition of the JAK/STAT pathway promotes replication of Hantaan virus ( 72 ). On the other hand, in addition to its function in antiviral IFNs production, the role of JAK/STAT signaling in the release of a wide array of pro-inflammatory cytokines during SARS-CoV-2 infections has been the center of attention for various research groups across the globe.…”
Section: Discussionmentioning
confidence: 99%